2022
DOI: 10.17509/jsl.v5i3.43546
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality and Animation Supported-STEM Activities in Grades K-12: Water Treatment

Abstract: Animation is used to increase the interest and engagement of students in the learning environment. Animation is exciting and fun, and using animation, abstract concepts are easy to present, display, and convey to students. Augmented reality, like animation, can help make it easier to understand abstract concepts. In many areas, augmented reality is used in education since it perfectly integrates virtual content with the natural world. STEM education is one of the areas where augmented reality can be used effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
1
0
1
Order By: Relevance
“…In addition, the results of the study found that the use of STEM-based android applications with the help of Augmented Reality increased learning outcomes for students, as seen from the N-gain scores of the experimental class in the high category. This is in line with research by Usta [40] that the use of animation is intriguing and fun, and by using animation, abstract concepts are easily presented, displayed, and conveyed to students. This study found that STEM education is an area where Augmented Reality can be used effectively.…”
Section: Based On Tablesupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the results of the study found that the use of STEM-based android applications with the help of Augmented Reality increased learning outcomes for students, as seen from the N-gain scores of the experimental class in the high category. This is in line with research by Usta [40] that the use of animation is intriguing and fun, and by using animation, abstract concepts are easily presented, displayed, and conveyed to students. This study found that STEM education is an area where Augmented Reality can be used effectively.…”
Section: Based On Tablesupporting
confidence: 86%
“…The study found that using a STEM approach improved students' thinking at school [34]. Furthermore, Usta and Ultay et al also researched AR with a STEM approach, which found that AR animation was exciting and fun, abstract concepts were easy to present, and that STEM education was one area where Augmented Reality could be used effectively [40]. Various benefits have been found in previous relevant research.…”
Section: Introductionmentioning
confidence: 99%
“…Bunu sağlayabilmek için teknoloji destekli eğitim araştırmalarının, bu anlamda da özellikle STEM'in eğitim alanında popülerliliğin arttığı dikkati çekmektedir. Son yıllardaki çalışmalar incelendiğinde STEM eğitimi odaklı çalışmaların öğrencilerin 21. yüzyıl becerilerini geliştirmede oldukça etkili olduğu görülmektedir (Alberta Education, 2007;Beane, 1991;Bybee, 2013;Dönmez Usta & Ültay, 2022;Ültay vd., 2021;Martín-Páezet vd., 2019). STEM, fen, teknoloji, mühendislik ve matematik alanlarını kapsayan ve bunları kullanarak günlük yaşam problemlerine özgün/yaratıcı çözümler getirmeyi amaçlayan bir eğitim yaklaşımıdır (Ring vd., 2017).…”
Section: Introductionunclassified